Measurement of dynamic and static properties of residual soil using a modified cyclic triaxial apparatus - Cheng, Zhuoyuan (2024)
A cyclic triaxial apparatus was modified to determine the dynamic and static properties of a residual soil at different degrees of saturation. The modification includes addition of bender elements, local displacement transducers (LDTs), and proximity sensors. Improvements were made to the LDT setup using 3D-printed hinges to reduce slippage of the LDT. The primary (P) and secondary (S) wave velocities and the damping ratio (ξ) were obtained from the bender element signals using time domain first arrival times and the Hilbert transform method, respectively. Results of the shear modulus normalized with small-strain shear modulus (G/Gmax) and ξ with shear strains were obtained, and they showed good agreement with similar soils in the literature. The Poisson's ratio obtained from wave velocities, LDTs, and the proximity sensors shows a reasonable trend and value. The soil specimens were sheared to failure after the cyclic loading. Saturated specimens were sheared under the consolidated undrained condition, whereas unsaturated specimens were sheared under the constant water content condition. Results of effective shear-strength parameters (φ′ and c′) were observed to fall within the range of similar soils found in the literature. The unsaturated specimens' φ were observed to be similar to the saturated specimens' φ, and the cohesion intercept increased as degree of saturation decreased.